2010
DOI: 10.1002/prca.200900119
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease proteomics

Abstract: Non-alcoholic fatty liver disease (NAFLD) is an important cause of chronic liver injury that has gained concern in clinical hepatology. The principal aim of this study was to find differences in protein expression between patients with NAFLD and healthy controls. Changes in protein expression of liver samples from each of the three groups of subjects, controls, non-alcoholic steatosis, and non-alcoholic steatohepatitis (NASH), were analyzed by two dimensional differential in gel electrophoresis (DIGE) combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 50 publications
(55 reference statements)
7
51
1
Order By: Relevance
“…The ASS gene products were not changed and thus were not rate limiting in NASH. The changes in CPS enzyme protein are in accordance with a recent study on proteomics in human NAFLD in which CPS in liver samples from patients with NASH was found to be downregulated (33).…”
Section: Discussionsupporting
confidence: 89%
“…The ASS gene products were not changed and thus were not rate limiting in NASH. The changes in CPS enzyme protein are in accordance with a recent study on proteomics in human NAFLD in which CPS in liver samples from patients with NASH was found to be downregulated (33).…”
Section: Discussionsupporting
confidence: 89%
“…Rodríguez-Suárez et al [24] analysed the protein expression of liver samples with DIGE in combination with MALDI TOF/TOF. Ten of the proteins were further validated by Western blotting to confirm the observed changes of protein expression [24] .…”
Section: Metabolic Pathwaysmentioning
confidence: 99%
“…Ten of the proteins were further validated by Western blotting to confirm the observed changes of protein expression [24] . This study has successfully demonstrated that both serum concentration of carbamoyl phosphate synthase 1 (CPS1) and 78 kDa glucose-regulated protein (GRP78) decreased gradually from cholecystectomy controls with normal liver function and histology subjects to steatosis and NASH patients [24] . Further validation of CPS1 and GRP78 in higher number of patients is still warranted.…”
Section: Metabolic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify new biomarkers, Rodríguez-Suárez and colleagues performed protein expressions of liver biopsies in three groups of subjects that included controls and patients with either NAFLD or non-alcoholic steatohepatitis (NASH). The liver samples were analyzed using two-dimensional differential gel electrophoresis (DIGE) combined with MALDI TOF/TOF analysis [93]. A total of 43 proteins exhibiting significant differential expression was identified, including 22 comparing steatosis samples versus controls, and 21 comparing NASH versus controls.…”
Section: Proteomics Examplementioning
confidence: 99%